Utilization review of the use of BACTEC PLUS high-volume blood culture bottles. - Porter, R C (1993)
The BACTEC PLUS 26 (NR26) (Becton Dickinson, Towson, Md.) high-volume blood culture bottle replaced the less expensive smaller-volume NR6A bottle in our hospital. An audit carried out several months after their introduction revealed that only 17.5% of the NR26 bottles received the required blood volume. Several audits and educational programs were required in order to achieve a compliance rate of > 60%.